Factors Influencing The Career Choice Of Students At Secondary School Level In Rawalpindi - Memoona Khalid, Dr. M. Imran Yousuf, Dr. Muhammad Imran (Migration Letters, 2024)
This study investigates the factors influencing career decisions among secondary school students in Rawalpindi. It utilizes a quantitative research approach, targeting all secondary-level government schools in the city. Data from 384 students (207 girls and 177 boys) was collected through questionnaires, employing a simple random sampling technique. The research design is descriptive, employing a survey-based methodology. SPSS software (version 21) was utilized for data analysis, including calculating mean, standard deviation, and percentages. The findings, presented in tabular form, indicate that societal influences play a significant role in guiding students through the career selection process. Additionally, the study highlights further factors influencing career decisions among secondary school students in Rawalpindi. The conclusions drawn from this research provide valuable insights for educators, policymakers, and stakeholders involved in guiding students towards successful career paths. By identifying career choices, investigating influencing factors, comparing and identifying decision-making strategies, the study provides valuable insights that can inform targeted interventions, policies, and programs aimed at empowering students in making informed and fulfilling career decisions. Ultimately, such efforts contribute to the holistic development and well-being of students as they transition into the workforce and pursue their professional aspirations.